Answer:
11
Step-by-step explanation:
5+6 = 11
1 hour=1/6+1/6+1/6
1 hour=3/6
1 hour=1/2
for every hour, the snail moved 1/2 a foot
Answer:
Step-by-step explanation:
(47+1)/(3-6) = 48/-3 = -16
y + 1 = -16(x - 6)
y + 1 = -16x + 96
y = -16x + 95
Answer:
I'm sorry but no idea
Step-by-step explanation:
No idea
<h2>y + 1 = -3(x - 10)</h2>
Here's the formula:
y - y1 = m(x - x1)
Substitute numbers accordingly:
y1: so 1 goes in the y1 spot (you switch the signs because it was already negative)
x1: and 10 goes to the x1 spot
m: -3 belongs in m